Moral Education in Islamic Perspective: A Preventive Solution to the Moral Crisis of Adolescents - Guruh Oktasatria Rachma Putra; M. Agus Nurohman; Wakib Kurniawan (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
This research aims to analyze Islamic teachings on morality derived from the Qur’an, Hadith, and scholarly interpretations, identify the key factors contributing to the current moral decline among youth, and evaluate how Islamic moral education can effectively address these issues.The moral crisis among adolescents is an increasingly worrying problem, marked by the increase in deviant behavior, such as bullying, promiscuity, and abuse of technology. Moral education in an Islamic perspective offers a preventive solution through instilling the values of faith, kindness, and social responsibility. This article aims to examine the strategic role of Islamic moral education in shaping the character of adolescents with noble character. Using a qualitative approach through a literature study, this article explores the concept of moral education, moral problems of adolescents, and the implementation of moral education in the context of formal and non-formal education. The results of the study show that Islamic moral education that is implemented holistically can strengthen the moral resilience of adolescents.